Identification of Bacteria in Kawista Leaves (Limonia acidissima L.) - Jamiatul Aulia; Nining Purwati; Sri Sofiati Umami (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Bacteria are unicellular prokaryotic microorganisms which are abundant in nature. This study aims to isolate and identify bacteria present in the leaves of Kawista (Limonia acidissima L.). Method: The identification process was carried out in a microbiology analyzer with the help of the BD Phonix M50 identification tool. The study was conducted at the West Nusa Tenggara Province Testing and Calibration Laboratory for Health, using kawista (Limonia acidissima L.) leaves obtained from West Sumbawa Regency. Results: The results showed eight bacterial isolates were found including Bacillus sp, Bacillus megaterium, Staphylococcus sp, Staphylococcus epidermidis, Staphylococcus capitis, Streptococcus oralis, Leuconostoc mesenteroides spp. mesenteroides, and Shewanella putrefaciens. Conclusion: Diversity of types of bacteria can be studied through the process of identification. This study aims to isolate and identify bacteria found in kawista leaves. The identification method is carried out in a microbiology analyzer with the help of the BD Phonix M50 identification tool. Bacteria found on the leaves of kawista (Limonia acidissima L.) consist of a group of endophytic bacteria, lactic acid bacteria, metal reducing bacteria, and pathogenic bacteria.